2008
DOI: 10.1097/rli.0b013e3181559932
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Small Contrast Enhancing Breast Lesions in Dynamic Magnetic Resonance Imaging Using a Combination of Morphological Criteria and Dynamic Analysis Based on Unsupervised Vector-Quantization

Abstract: Purpose-To evaluate the diagnostic value of breast magnetic resonance imaging (MRI) in small focal lesions using dynamic analysis based on unsupervised vector quantization in combination with a score for morphologic criteria.Materials and Methods-We examined 85 mammographically indetermintate lesions (BIRADS 3-4; 47 malignant, mean lesion size 1.2 cm; 38 benign, mean lesion size 1.1 cm). MRI was performed with a dynamic T1-weighted gradient echo sequence (1 precontrast and 5 postcontrast series). Lesions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…Finally, in a clinical study on 85 small mammographically indetermintate lesions, it could be demonstrated that dynamic analysis using our vector quantization approach alone resulted in a higher diagnostic accuracy when compared to a combined morphologic and dynamic analysis [128].…”
Section: Dynamic Mr Image Time-series Analysis In Breast Cancer Diagnmentioning
confidence: 96%
“…Finally, in a clinical study on 85 small mammographically indetermintate lesions, it could be demonstrated that dynamic analysis using our vector quantization approach alone resulted in a higher diagnostic accuracy when compared to a combined morphologic and dynamic analysis [128].…”
Section: Dynamic Mr Image Time-series Analysis In Breast Cancer Diagnmentioning
confidence: 96%
“…However, not many studies have focused on evaluating the value of DCE-MRI in small lesions which may not exhibit typical characteristics of benign and malignant tumors [13]. Accurate diagnosis of such small lesions is clinically important for improving disease management in patients, where evaluating the dignity of breast lesions as being benign or malignant is specifically challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The best hyperplane is the one that maximizes the distance (margin) of the two parallel hyperplanes defined in Equation 14. Since the distance of a hyperplane to the origin is b w , we want to maximize 2 w .…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…, n in their d dimensional domain in two classes v i ∈ {M, B}. First, let us assume that our data set is linearly separable and that we can find a pair ( w, b) that fulfills 14) http://asp.eurasipjournals.com/content/2013/1/157…”
Section: Support Vector Machinesmentioning
confidence: 99%